Energy justice and the co-opting of indigenous narratives in U.S. offshore wind development. (June 2022) - Bacchiocchi, Eana; Sant, Ingrid; Bates, Alison
Abstract: The possibility of substantial offshore wind energy development in the United States (U.S.) is rapidly advancing. Several offshore wind projects have been proposed proximate to federally-recognized tribal territory. Historically marginalized, indigenous communities have for centuries experienced injustices during the expansion of the U.S. energy system. Few studies have systematically examined the responses of indigenous communities to offshore wind, and little is known about the ways that indigenous concerns are leveraged by non-members to advance a position advocating for or against offshore development. In this study, we examine the discourses that surround indigenous communities through legally mandated decision-making processes for two proposed offshore wind projects in the northeast U.S. We show that narratives surrounding indigenous stakeholders in the offshore wind scoping process can be thematically identified as: 1. religious, cultural, and spiritual value, 2. land and identity, and 3. process and procedures . However, the concerns and perspectives of indigenous communities are mostly brought forth by non-group members, and were found to be leveraged or diminished by non-indigenous individuals pushing anti- or pro-offshore wind sentiment. This reveals the finding that indigenous concerns are being co-opted or sidelined through formal and legal decision-making processes in the U.S. The results indicate that the formal consultation process failed to meet standards of energy justice by inadvertently giving outsize voice to lesser impacted communities. Therefore, our study cautions that energy justice is not achieved solely through "inclusive" processes and decision-makers should be diligent in considering the multi-faceted aspects of justice.